Overview of MICP Geotechnical Engineering Applications and Development Prospects - Wang, Xiaoqiang; Yuan, Xiaoqing (Journal of Research in Science and Engineering, 2025)
This study examines the research directions and potential of geotechnical engineering applications utilizing MICP. Due to the effective application of this technology in various geological reconstruction and engineering projects, coupled with the controllable and universal microbial induction process, it serves as an alternative green technology to a significant degree. Current research indicates that the urea hydrolysis reaction is extensively utilized due to its high efficiency and ease of control, yet its by-product ammonia may pose environmental pressures; meanwhile, the sulfate reduction reaction encounters issues related to the generation of toxic gases. In comparison, although iron reduction and denitrifying bacteria are more environmentally friendly, there remains room for improvement in sedimentation efficiency and gas production control. At the practical application level, MICP has been employed in soil remediation, soil reinforcement, and pollution control, demonstrating notable engineering value. However, technical challenges arise, including limited improvement effects on fine-grained soil, significant discrepancies between laboratory research outcomes and actual environmental adaptability, as well as research difficulties stemming from the complexity of microbial behavior. Nevertheless, MICP holds potential in achieving the carbon peak goal, thanks to its environmental friendliness, low energy consumption, and high efficiency. Through innovative approaches such as multi-material composite improvement, the technical adaptability and application effectiveness can be further enhanced. Future research should integrate interdisciplinary strengths to optimize bacterial selection and process design, thereby promoting the widespread application of MICP in geotechnical engineering.